Evaluation Mechanical Properties of Repaired Polyamide Dentures at Different Processing Techniques and Surface Treatment - Haider Ibrahim Khalil Abdel Wazni; Amal Abdul Latif Rashid (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
Background: Polyamide denture base materials have gained prominence in dentistry due to their superior attributes compared to traditional acrylic materials. However, the susceptibility of polyamide dentures to fractures necessitates exploration of repair, replacement, and reinforcement methods. Effective denture rehabilitation requires enhancing tensile and transverse strength.Methods: This study utilized 160 acrylic resin samples. The control group included 40 specimens with and without fusing material integration, representing fractured and intact scenarios. The remaining 120 specimens underwent meticulous repair through three approaches: Reinjection nylon repair (RiNR), Recycling Manual heating (spruing) repair (RcNHR), and Manual heating nylon (NHR) repair, each with American and Russian fusing materials. Rigorous tensile and transverse strength evaluations were performed. Results: Techniques augmenting tensile and transverse strength (RcNHR, NHR, RiNR) were significantly effective compared to untreated fractures (C2) for both fusing materials. The control group (C1) consistently exhibited higher strength than C2. RiNR exhibited paramount strength, with American-treated RcNHR showing lower tensile strength, and Russian-treated NHR showing reduced transverse strength. Russian and American treatments showed no significant differences in RcNHR and RiNR, but differences emerged in NHR. Conclusion: Implementing flexible materials enhances polyamide denture strength. Reintegration through reinjection and manual heating with sprue-material yielded positive outcomes. RiNR achieved the highest strength. Russian and American treatments showed no notable differences in RcNHR and RiNR, with variations seen in NHR. This study suggests potential for refining mechanical properties and methodologies, advancing denture restoration practices.